DEVELOPING ASSESSMENT INSTRUMENTS FOR ENGLISH LITERACY IN BLENDED LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS - Wijaya, Eka Anastasia; Ratminingsih, Ni Made; Utami, IGA Lokita Purnamika (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This research intended to develop assessment instruments for English literacy in blended learning. The study employed survey, observation, interview, and document study as the methods with a questionnaire, observation checklist, interview guide, and school document as the instruments to collect the data framed within RnD design with the 4D model by Thiagarajan et al. The developed instruments were categorized as ‘very high validity’ and ‘very good’ for their content validity (1.00) and product quality (96% and 98%) by the two judges. It indicates that assessment of learning, assessment for learning, and assessment as learning combined with authentic materials are necessary to improve the learning process as well as the students’ English literacy skills. It also implies that English teachers need to highlight the use of assessment for learning and assessment as learning since those assessments lack attention previously.